1975
DOI: 10.1126/science.49925
|View full text |Cite
|
Sign up to set email alerts
|

Myelination Inhibiting and Neuroelectric Blocking Factors in Experimental Allergic Encephalomyelitis

Abstract: Sensitization of Lewis rats with whole central nervous system tissue or with purified myelin induced both experimental allergic encephalomyelitis (EAE) and a serum factor which inhibited myelin formation in vitro. Sensitization with the encephalitogenic factor, myelin basic protein, induced EAE, but not the myelination inhibition factor. Sensitization with cerebroside induced neither EAE nor myelination inhibition factor. The serums from control animals without EAE as well as from animals sensitized with all o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
2

Year Published

1976
1976
1999
1999

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 17 publications
2
13
2
Order By: Relevance
“…It is in marked contrast with recent tissue culture studies (Seil et al, 1975) in which blocking activity was equally abundant in a variety of control sera. A possible explanation of these studies is that the electrical activity found in tissue culture systems is relatively more labile and sensitive to a component of normal serum which the frog spinal cord is either insensitive to, or which is masked by the VRR potentiating effect characteristic of normal serum.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…It is in marked contrast with recent tissue culture studies (Seil et al, 1975) in which blocking activity was equally abundant in a variety of control sera. A possible explanation of these studies is that the electrical activity found in tissue culture systems is relatively more labile and sensitive to a component of normal serum which the frog spinal cord is either insensitive to, or which is masked by the VRR potentiating effect characteristic of normal serum.…”
Section: Discussioncontrasting
confidence: 96%
“…increase in VRR. In no case was the VRR significantly decreased by normal serum, in contrast with the results obtained on cultured CNS tissue (Seil et al, 1975(Seil et al, , 1976. 682 Our data on the potentiation by control sera agree fairly well with that of Cerf and Carels (1966) who obtained an average 42% increase (range 9%/O to 84%) in VRR in 12 preparations.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The suspicion that such factors may exist originated with a study showing that sera from animals with experimental autoimmune encephalomyelitis or from MS patients during acute exacerbation, blocked re£ex activity in cultured central nervous system (CNS) tissue within minutes of exposure and in a complement-dependent manner (Bornstein & Crain 1965). The study was quite small and included few controls, but it was followed by a series of studies which reached similar conclusions (Cerf & Carels 1966;Carels & Cerf 1969;Lumsden et al 1975a,b;Schauf et al 1976 and some others which threw doubt on the interpretation of the data (Crain et al 1975;Seil et al 1975Seil et al , 1976, claiming that the blocking activity was not speci¢c to MS. Where present, the conduction block appears to be contained within the IgG-containing fraction of serum (Crain et al 1975; and it is diminished by plasma exchange Stefoski et al 1982). However, if antibodies are involved, they probably act by means other than demyelination, since the blocking activity is both prompt and reversible.…”
Section: (Iv) Neuroelectric Blocking Factorsmentioning
confidence: 95%
“…Kies et a1 [48] similarly demonstrated that most sera from myelin basic protein-sensitized guinea pigs with high titers of anti-basic protein antibody fail to prevent myelination upon application to cerebellar cultures from the time of explanation. This demonstration was repeated with sera from subhuman primates [73], rabbits [7 11, and Lewis rats [74] [37,42] might be due to contamination with minute amounts of other myelin fractions. The possibility remains that cerebroside induction of serum antimyelin factors is a phenomenon peculiar to rabbits, and studies are under way to examine this question.…”
Section: Eae and Serum Antimyelin Activitymentioning
confidence: 91%